Thin-walled ware from recent excavations in the East Bath complex at Labraunda (Milas, Turkey) - Streinu, Alina (Rei Cretariae Romanae Fautorum Acta, 2022)
The paper presents thin-walled fine wares discovered during recent excavations at Labraunda, focusing on the Knidian-type cups. These small vessels come in various shapes and fabric, posing the question of their origin, which are made in Knidos and which are imitations. The discussion on these cups entails their typological evolution and issues related to possible centers imitating the shape and the means by which they arrived at the site. There are four variants identified according to shape and six types of fabrics. Corroborating with other finds and research in other sites with possible imitations (Cos, Rhodes, Pergamum), we discuss the possibilities of how these cups arrived at Labraunda and why.